Fatigue failure investigation on offshore pipelines with 3D cracks at the welding joints - Yoon, Sang Ryun (Nanyang Technological University, 2023)
Offshore pipeline weld joints frequently have small cracks that can be seen and recognized. The integrity and safety of pipelines are seriously threatened by these microscopic cracks because they may spread more quickly and start to combine with one another under conditions of continuous loading. In present report, ANSYS Workbench was used to analyses to simulate the embedded elliptical crack within welding joint and its result. The finite element method has been used in the current work to predict the fatigue behavior of two 3-D interacting semi-elliptical fractures under a cyclic tensile load. By analyzing stress intensity factor (SIF) values and associated parameters from numerical simulation results, the rate of fatigue crack growth has been examined. The objective of this report is to investigate and conduct simulation to determine the behavior of how an embedded elliptical fracture would grows based on the welding and pipe materials.